Legal Protection of Persons with Mental Disorders in Health Services in Accordance with Laws and Regulations in Indonesia - Zanuba, Sherly; Saputri, Maretha Maharani; Sami'an, Sami'an (Riviera Publishing, 2025)
This study aims to examine the role of the Pekalongan City Social Service in synchronizing legal protection arrangements for people with mental disorders (ODGJ, Orang dengan Gangguan Jiwa) and to identify forms of legal protection in health services within the framework of Indonesian laws and regulations. The research employs a normative legal research approach, focusing on laws, legal methods, legal principles, and regulations, as well as expert opinions. The problem approach used in this study includes a legislative approach and a conceptual approach. The legislative approach involves reviewing all relevant laws and regulations related to the issue at hand, while the conceptual approach examines theoretical frameworks and principles underlying legal protection for ODGJ. The research methods include the statute approach (analysis of laws and regulations) and an analytical approach, with a focus on inventorying laws and regulations, legal synchronization, and legal discovery in concreto. Based on the findings, it is concluded that the Pekalongan City Social Service has played a significant role in implementing the synchronization of legal regulations related to the protection of ODGJ. Forms of legal protection include ensuring access to standardized mental health services, rehabilitation, empowerment, elimination of shackling practices, availability of psychopharmacological drugs, the right to accurate medical information, protection from violence and discrimination, and the fulfillment of social and legal rights. These protections aim to improve the quality of life for ODGJ, guarantee their rights as citizens, and ensure equal treatment in all aspects of life.